Fast Recognition of Lecanicillium spp., and Its Virulence Against Frankliniella occidentalis - Zhou, Yeming; Zou, Xiao; Zhi, Junrui; Xie, Jiqin; Jiang, Tao (Frontiers in Microbiology, 2020)
Background: Frankliniella occidentalis (Thysanoptera: Thripidae) is a highly rasping-sucking pest of numerous crops. The entomogenous fungi of Lecanicillium spp. are important pathogens of insect pests, and some species have been developed as commercial biopesticides. To explore Lecanicillium spp. resources in the development of more effective F. occidentalis controls, efficient barcode combinations for strain identification were screened from internal transcribed spacers (ITS), SSU, LSU, TEF, RPB1, and RPB2 genes. Results: Six genes were used to reconstruct Lecanicillium genus phylogeny. The results showed that ITS, TEF, RPB1, and RPB2 could be used to identify the strains. All phylogenetic trees reconstructed by free combination of these four genes exhibited almost the same topology. Bioassay studies of a purified conidial suspension further confirmed the infection of second-instar nymphs and adult female F. occidentalis by seven Lecanicillium strains. L. attenuatum strain GZUIFR-lun1405 was the most virulent, killing approximately 91.67% F. occidentalis adults and 76.67% nymphs after a 7 d exposure. L. attenuatum strain GZUIFR-lun1405 and L. cauligalbarum strain GZUIFR-ZHJ01were selected to compare the fungal effects on the number of eggs laid by F. occidentalis. The number of F. occidentalis nymphs significantly decreased when F. occidentalis adults were treated with L. cauligalbarum strain GZUIFR-ZHJ01. Conclusions: The combination of ITS and RPB1 could be used for fast recognition of Lecanicillium spp. This is the first report of the pathogenicity of L. attenuatum, L. cauligalbarum, L araneogenum, and L. aphanocladii against F. occidentalis. Additionally, L. cauligalbarum strain GZUIFR-ZHJ01 caused high F. occidentalis mortality and inhibited the fecundity of the pest.